2015
DOI: 10.1111/phn.12189
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Health Risk Factors in Workplaces of Low and Middle‐Income Countries

Abstract: ObjectiveTo reduce risk factors in workplace settings in low and middle-income countries DesignWorkplace interventions were utilized as part of the Community Interventions for Health (CIH) program, a non-randomised, controlled study undertaken in three communities in China, India and Mexico.Sample 45 industrial, 82 health and 101 school workplace settings with a target population of 15,726. Two independent cross-sectional surveys of workers were conducted at baseline and follow-up, after 18-24 months of interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…Furthermore, community-based studies from Kerala reported a comparatively higher NCD risk factor prevalence [10]. Interventions among working population were found to be effective in modifying the NCD risk factors in the state [11] and other parts of India [12]. In a study from rural Kerala, 24.4% of hypertensives were aware of their condition, 19.7% were treated, and only 6.4% had their blood pressure under control [13].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, community-based studies from Kerala reported a comparatively higher NCD risk factor prevalence [10]. Interventions among working population were found to be effective in modifying the NCD risk factors in the state [11] and other parts of India [12]. In a study from rural Kerala, 24.4% of hypertensives were aware of their condition, 19.7% were treated, and only 6.4% had their blood pressure under control [13].…”
Section: Introductionmentioning
confidence: 99%
“…These interventions should affect physical activity, although similar interventions in workplaces in the CIH sites showed no significant changes (Anthony et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown community‐based interventions had an impact on risk factors in the workplace (Anthony et al . ) and community (Dyson et al . ) and this study shows further evidence for its effectiveness in clinical areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies on the health management of workers by the occupational health nurses have been conducted, however, they only dealt with the management of hypertension, antialcoholism, and cardiovascular diseases (Anthony, 2015;K. S. Kim, 2009;Kwon et al, 2011;Osondu et al, 2016;Rebold et al, 2015).…”
mentioning
confidence: 99%